ISSUES OF EDUCATION, SELF-EDUCATION AND READING IN THE PERIODICALS OF THE LITHUANIAN DIASPORA IN THE UNATED STATE (UP TO 1904) - Misiūnas, Remigijus (Knygotyra, 2017)
The purpose of this article is to provide an analysis of the situation of education and self-education as part of informal learning up to the year 1904 among members of the Lithuanian diaspora in the United States, based on the Lithuanian periodicals published during the period in question, and to evaluate its significance on publishing. The objectives were to explore the efforts of the diaspora to establish their own institutions for the education of children and adults and to analyze the importance of press in promoting education and self-education as well as the significance of education and informal learning on the development of publishing. This is the first attempt to conduct relevant research on the basis of the material at our disposal, collected from the press of the Lithuanian diaspora of that period. Although the situation of education and reading was far from satisfying the needs of the then contemporaries, the literacy rate in the community of Lithuanian emigrants in the USA kept growing (of particular importance was the focus on women’s education and reading). Such a situation was predetermined by the pursuit of economic prosperity (initial education and training and the knowledge of English contributed to getting a better job). An increasing concern over the children‘s welfare resulted in a growing number of schools. Ideological struggle within the diaspora community was also a significant factor. Furthermore, one should not forget curiosity and leisure (perhaps the best indicator is the growing number of emigrants who learned to read inspired by the poor quality of literature at hand). Even though a certain number of institutions for the education of children were established, they were restricted only to one type of schools, namely, parochial elementary schools, and their development was hindered by ideological quarrels, disagreements over the content of teaching and compliance with the requirements of the historic period in question. Due to this, and for other reasons, a large number of emigrants sent their children to American public schools or parish schools of other foreign nationals living in the United States, while the number of Lithuanian schools at that time exerted little influence on the development and output of book publishing. Likewise, it cannot be argued that publishing was directly influenced by the creation of evening schools, the more so that English textbooks were used in them. That being said, it has to be stated that the importance of a part of the publishing output was evaluated according to its appropriateness to reading by those attending the schools in question, initially for learning, and then for self-study purposes. The same applies to some of the books published in Eastern Prussia and imported to the United States. Self-education was of particular importance to publishing, as the press was considered its main source. In addition, expatriate societies, which identified the promotion of education and reading as one of their goals, were at times engaged in publishing activities on their own. However, it has to be said that the situation was significantly influenced by a deepening split within the Lithuanian diaspora from the ideological point of view. Representatives of different trends voiced their own views on self-education and reading (what should be read and what should be forbidden). At the same time, this division encouraged the publication of literature aimed at spreading their own ideas, while at the same time was suitable for self-education and reading. True, the repertoire of literature published and the influence of education and self-study needs on publishing both from the quantitative and qualitative point of view require a separate in-depth study. At the turn of the 20th century, the Lithuanian diaspora could boast quite a significant selection of literature at its disposal and a large number of members who had either basic education or were sufficiently educated. In addition, some embryonic roots in the structure of education and self-education could already be discerned, which grew over time and contributed to the development of publishing.